Análisis de barreras rompevientos aplicadas a la restauración agroecológica de suelos con producción de maíz, en el sector de San José de Pichul, parroquia Eloy Alfaro, cantón Latacunga. - Bonilla Hinojosa, Diana Carolina (2022)
Soil degradation is a silent crisis that is advancing rapidly, it is a problem that tends to be ignored by governments and the population, Latacunga has 32% of eroded areas in the urban area, therefore, this research is aimed at evaluating the effectiveness of windbreaks applied to the agroecological restoration of soils with corn production, in the San José de Pichul sector, Eloy Alfaro parish, Latacunga canton. The experimental descriptive methodology was used, delimiting an area of 815.30 m2 with corn cultivation and the presence of a perimeter barrier distributed in three rows in a space of 84 m2. An inventory of species that make up the barrier was generated, where the presence of Acacia melanoxylo, Tecoma stans, Callistemon citrines and Retama sphaerocarpa L. was recorded. With the application of Anova - Tukey at 5%, the relationship between species was identified, being Acacia melanoxylo predominant for its leaf area and total height, while Retama sphaerocarpa L. was the species with the least adaptation within the barrier. On the other hand, the presence of macro-micronutrients in the soil the sample with the barrier protection obtained a significant difference of Nitrogen (N) 7.5 ppm, Phosphorus (P) 101.7 ppm, Sulfur (S) 7.8 ppm, Boron (B) 0.01 ppm, Potassium (K) 0.16 meq/100g, Calcium (C) 1.44 meq/100g, Magnesium (Mg) 0. 22 meq/100g, Zinc (Zn) 2.1 ppm and Manganese (Mn) 1.3 ppm, with the exception of Copper (Co) 0.7 ppm and Iron (Fe) 19 ppm, while in the corn crop there was an affectation to its growth, due to the edge effect of the barrier, however, 39% of the total corn production was obtained, with ears of better boom. It is concluded that the barrier protects an area of approximately 1720 m2 because it does not present spaces in its structure, contributing to the reduction of desertification and increasing the amount of nutrients, allowing the agroecological restoration of the soil and affecting the improvement of corn production.